Preparation, characterization, and water-sorption study of polyvinyl alcohol based hydrogels with grafted hydrophilic and hydrophobic segments - Shukla, S.; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2005)
The interpenetrating polymer network hydrogels based on poly(vinyl alcohol) were obtained by graft copolymerization of acrylamide and styrene onto polyvinyl alcohol in the presence of N,N'-methylene bisacrylamide as a crosslinking agent. The hydrogels were characterized by optical microscopy, scanning electron microscopy, infrared spectral analysis, differential scanning calorimeter, and thermogravimetric analysis. The hydrogels showed enormous swelling in aqueous medium and displayed swelling characteristics, which were highly dependent on the chemical composition of the hydrogels and pH of the swelling medium. The kinetics of water uptake and the mechanisms of water transport were studied as a function of composition of the hydrogel and pH of the swelling medium. (C) 2005 Wiley Periodicals, Inc.
Keywords: Characterization; equilibrium swelling; grafting; IPN hydrogels; polyvinyl alcohol